Ny udgave af Føroysk-donsk orðabok - Hansen, Zakarias Svabo; Joensen, Hans (Nordiske Studier i Leksikografi, 2005)
The topic ofthis paper is the new edition ofthe Faroesc-Danish dictionary which is in progress for the time being. The paper starts by giving a briefhistorieal outline over Faroese bilingual dictionaries chronologically. Then the authors deal with the sclcction of entries in the new edition of Faroese-Danish dietionary. Because this edition is based on the monolingual Faroese dictionary the qucstion is under discussion, whethcr it is rcasonablc to use a monolingual dictionary as a basis at all. How successfully are the Faroese cntries translated into Danish, and how about the lexicographical examplcs which arc connected to the entries: arc thcy adcquate to use in such a modem dictionary as this onc is ment to bc? Thesc arc somc ofthc questions which this papcr trics to throw light on.